The ILO's Role in Fulfilling Garment Workers' Rights through the BWB II Program After the Rana Plaza Collapse - Heren Budi Mulia Kusmawan; Resa Rasyidah (Insignia: Journal of International Relations, 2023)
The collapse of the Rana Plaza building in Bangladesh on April 24, 2013, was recorded as the worst industrial accident ever. This accident killed at least 1,132 and injured more than 2,500. This incident made the world aware of the poor working conditions in Bangladesh's garment industry sector. In addition, many workers do not even get their working rights, so there are actions or demonstrations carried out by workers, demanding their rights. The demonstration even received support from activists or outsiders???. Bangladesh is a developing country with the second largest textile exporter after China. Bangladesh's garment industry accounts for about 80 percent of the total revenue in the country's manufacturing sector. This study discusses the role of the International Labor Organizations (ILO) in fulfilling the rights of garment workers through the Better Work Bangladesh (BWB) program after the collapse of Rana Plaza. To explain this case, the author uses the role theory of international organizations by Kelly Kate S. Pease. According to Pease, state problems can be solved with the help of external parties by acting as problem solvers, collective art mechanisms, capacity builders, and aid providers. Research shows that the ILO has an effective role in fulfilling the rights of Bangladeshi garment workers through the Better Work Bangladesh Phase II Program, in creating better or more prosperous labor conditions by cooperating with several internal and external parties. Keywords: Better Work Bangladesh (BWB), labor, garment, ILO